Economies of greed in 'late Pynchon': America and the logic of capital. Issue 3 (16th March 2019) - Berressem, Hanjo
ABSTRACT: On the theoretical backdrop of Mike Davis's Ecology of Fear, Michel Foucault's 'Of Other Spaces', Félix Guattari's Schizoanalytic Cartographies and Gilles Deleuze's 'Postscript on the Societies of Control', this essay traces how Pynchon addresses the relentless capitalisation of life and politics. Against the idea that his late work is 'Pynchon Lite', the essay argues that Pynchon's overall poetics and ethics, have, if anything, become even more strident, with Bleeding Edge the most bitter and angry novel he has written so far; a true 'late' work, a Jeremiad that, somewhat like Goya's pinturas negras, throws reality into stark and clear relief. At the centre of the discussion is the notion of greed as an obscure compulsion to gather wealth beyond 'that which is enough'. Of all living creatures, only humans have developed economies of infinite greed. As both greed and economy are time- and site-specific, Pynchon provides carefully researched chronologies and geographies of the two in order to adequately address their interaction in particular historical moments. With his 'tales of dispossession and betrayal', of which this essay traces in particular Inherent Vice and Bleeding Edge, Pynchon becomes one of many American writers and filmmakers who have made greed the centre of their concern.